Promoting housing affordability in Malaysia: can Islamic finance play a role? - Abd. Wahab, Norazlina; Hamzah, Hanissah; Mohd Yusof, Rosylin (2016)
This study seeks to investigate the relationship between affordability of home ownership in Malaysia and the role played by Islamic banks in promoting affordable financing.By establishing the link between affordability (measured by median house price/gross domestic product per capita) and total home financing by Islamic banks, the study seeks to decipher the issues of home ownership affordability.At the same time, it attempts to shed some light on the role of Islamic finance in providing a syariah based and syariah compliant alternative of a fair-priced home loan in promoting home ownership affordability in Malaysia. The study employs auto regressive distributed lag model on quarterly data from 2007 until 2014 to investigate the link between affordability and selected banking variables such as total home financing by Islamic banks and overnight policy rate.Data were extracted from the NationalV Property Information Centre and Bank Negara Malaysia Monthly Statistical Bulletin.Our findings suggest that Islamic banking plays a bigger role in promoting affordability by offering a fair and sustainable financing. The study highlights that Islamic banking to a certain extent has managed to live up to its ideals in achieving the maqasid al-shariah.